Sanitation Practices and Escherichia Coli Contamination in Sugarcane Ice: A Case Study from 16 Ilir Market in Palembang - Lisa Putri Sari; Desri Maulina Sari; Windi Indah Fajar Ningsih; Dini Arista Putri (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Sugarcane ice is a beverage susceptibleto be contaminated with bacteria such as E.coli from the processing stage to the final stage of serving. This study aimed to analyze the sanitary hygiene practices and E. coli content in sugarcane ice sold at 16 Ilir Market, Palembang. The method used was descriptive qualitative through observational research. There were 12 informants selected by purposive sampling and eight samples consisting of 4 samples of sugarcane ice and four samples of water used by the handlers. Laboratory results on sugarcane ice showed that 3 of the four samples tested were positive for E.coli, with 6.9 MPN/100 ml results and 1.1 MPN/100 ml. As for the water used by the handlers, all were detected negative for E.coli. The results showed that two handlers did not always wash their hands before processing sugarcane ice, and all handlers did not use special tools to take sugarcane stalks. 3 out of 4 servers still use water containers from disposable plastic containers, two servers do not have trash bins, and three servers have open sugar cane storage. The conclusion was that sugar cane ice's sanitary hygiene was still not good, and E.coli bacteria were found in sugar cane ice. The advice is that the server must be able to maintain personal hygiene, the cleanliness of the processing equipment used, and the cleanliness of the environment around the selling place to keep it clean.